Determination of Resistance Cumhuriyet-75 and Selimiye-95 Wheat (Triticum Aestivum L.) Varieties Against to Some Abiotic Stress Factories - Nezahat Turfan; Ekrem Mutlu (Turkish Journal of Agriculture: Food Science and Technology)
In this study, resistance mechanism of two wheat genotypes against salt, heavy metal, lime and drought (50%) treatments were investigated in summer Cumhuriyet-75 and winter Selimiye-95. According to results chlorophyll a, b, total chlorophyll and carotenoid level increased in FeCl3, drought and 225 mM NaCl in Cumhuriyet-75 but they were higher at NaCl, FeCl3 and ZnCl2 treatments in Selimiye-95 comparison to control. While H2O2 content rose all stres treatments in both varieties but Malondialdehyde (MDA) decreased in Selimiye with all applications. The amount of proline is lower in Cumhuiyet-75 but higher in Selimiye-95. Total soluble protein was found higher at salt concentartion and drought in both varieties. Ascorbate peroxidase (APX), Süperoxide dismutase (SOD) activity increased in salt and FeCl3 in Selimiye-95 but SOD ativity were higher at salt treatments in Cumhuriyet-75. And also in both varieties APX and Guaiacol peroxidase (GuPX) increased at FeCl3 but Catalase (CAT) were higher in only FeCl3 in Cumhuriyet-75. As a result Selimiye-95 showed tolerance to salt and FeCl3 with high photosynthetic pigment, proline and soluble protein content with lower MDA but it is sensitive to NiCl2 and drought. Whereas Cumhuriyet-75 cultivar is resistan to drought, FeCl3 and 225 mM NaCl depended on pigment, protein content and APX, CAT, GuPX and SOD activities. When all the data are taken into consideration, it was concluded that the responses of the varieties to the treatments changed according to the type and concentration of stress, and Selimiye-95 variety was tolerant compared to Cumhuriyet-75 variety.